Formulasi Krim Fraksi Ekstrak Daun Kemangi (Ocimum sanctum L) Sebagai Antibakteri Terhadap Staphylococcus aureus dan Escherichia coli - Saptawati, Tunik; Nurwidianingsih, Silvia; Girsang, Valentina; Aldila, Silvy (Jurnal Farmasi & Sains Indonesia, 2024)
Dermatosis vesiculobullosa is a public health issue that frequently affects Indonesian society and even the world. Current treatment often involves topical application of a cream to the infected area, utilizing chemical substances and traditional medicine. One of the plants that has antibacterial properties is basil. This study determined the excellence of hexane fraction cream made from basil leaves to kill Staphylococcus aureus and Escherichia coli bacteria. This experimental study used the maceration method with 96% ethanol is used for extraction, while the liquid-liquid extraction method for fractionation. The well diffusion method examined the antibacterial activity. The concentration of the n-hexane fractions is 15%, 30%, and 45%. The physical characteristic tests of the cream include organoleptic, homogeneity, pH, spreadability, adhesion, and viscosity. The researcher conducted a one-way Anova statistical analysis using the post hoc Duncan test. Basil leaf cream with n-hexane fractions at 15%, 30%, and 45% concentrations has an antibacterial activity of 20.09 mm (very strong), 21.47 mm (very strong), and 22.43 mm (very strong) against Staphylococcus aureus. It has an antibacterial activity of 20.10 mm (very strong), 22.83 mm (very strong), and 23.76 mm. The cream formulations with 30% and 45% n-hexane fraction effective at stopping the growth of Staphylococcus aureus and Escherichia coli, with a significance value of 0.000 (p<0.05).